A videodenzitometriával vizsgált korai myocardialis reperfúzió és a kései balkamra-funkció összefüggései. Eredmények acut myocardialis infarctus invazív ellátását követően - Sasi Viktor; Kalapos Anita; Gavallér Edit Henriette; Domsik Péter; Ungi Tamás; Zimmermann Zsolt; Nagy Ferenc Tamás; Horváth Tamás; Forster Tamás; Nemes Attila (2014)
Introduction: It is known that there is a relationship between myocardial perfusion and left ventricular function. Aim: The aim of the current study was to examine the relationship between myocardial reperfusion as assessed by videodensitometry on coronary angiograms following invasive treatment of ST elevation myocardial infarction and magnetic resonance imaging-derived late left ventricular function. Method: The study included 25 patients with ST elevation myocardial infarction. A quantitative parameter of myocardial (re)perfusion was calculated by the ratio of maximal density (Gmax) and the time to reach maximum density (Tmax) following invasive treatment. Magnetic resonance imaging was performed 387+/-262 days after ST elevation myocardial infarction for the evaluation of left ventricular function in all cases. Results: Significant correlations were demonstrated between left ventricular ejection fraction and Gmax (r = 0.40, p = 0.05) and Gmax/Tmax (r = 0.41, p = 0.04) following vessel masking. Conclusions: The results demonstrate significant relationship between densitometric Gmax/Tmax and late left ventricular function following ST elevation myocardial infarction. Orv. Hetil., 2014. 155(5), 187-193.